Advancing Healthcare EDI Interoperability Through Informatica Cloud B2B Gateway Quality Engineering - Devi Manoharan (International Journal of Computational and Experimental Science and Engineering, 2026)
Healthcare EDI operations face persistent quality challenges that undermine transaction success rates and revenue cycle performance. Partner onboarding delays, schema validation failures, mapping errors, and acknowledgment reconciliation gaps create operational inefficiencies. This paper presents a practitioner-oriented Quality Engineering framework specifically designed for Informatica Cloud B2B Gateway implementations. The framework delivers four reusable components: a validation taxonomy covering structural, semantic, code-set, and payer-specific rules; a partner onboarding test pack reducing integration timelines; an observability framework defining EDI-specific KPIs; and compliance-as-code approaches for HIPAA requirements. A detailed case study demonstrates framework application to 837 Professional claims processing, showing rejection rate reduction from 8.2% to 2.1%, resubmission turnaround improvement from 14 days to 3 days, and 340% first-year ROI. Organizations implementing these practices achieve measurable improvements in transaction success rates, operational efficiency, financial performance, and regulatory compliance. The framework provides healthcare IT teams with concrete, deployable components for immediate value realization.